2004
DOI: 10.1532/ijh97.03115
|View full text |Cite
|
Sign up to set email alerts
|

Phase III Study of Ranimustine, Cyclophosphamide, Vincristine, Melphalan, and Prednisolone (MCNU-COP/MP) versus Modified COP/MP in Multiple Myeloma: A Japan Clinical Oncology Group Study, JCOG 9301

Abstract: To investigate whether combination chemotherapy with vincristine, cyclophosphamide, prednisolone, and melphalan (COP/ MP) with the addition of ranimustine (MCNU) (MCNU-COP/MP) is superior to the slightly modified COP/MP (mCOP/MP) regimen in multiple myeloma (MM), a multicenter randomized study was performed. Two hundred ten patients with newly diagnosed, overt MM not treated with chemotherapy were enrolled from 32 institutions of the Lymphoma Study Group of the Japan Clinical Oncology Group and were randomized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 28 publications
1
1
0
Order By: Relevance
“…A Phase II study of COP (cyclophosphamide, prednisolone) -MP (melphalan, prednisolone) for untreated overt MM patients (JCOG8906) revealed a similar efficacy to those from the USA and Europe (48). A subsequent randomized Phase III study comparing modified (m)COP-MP with/without ranimustine for untreated overt MM (JCOG9301) revealed that addition of ranimustine to mCOP/ MP has no benefit for survival, despite improving the response rate and PFS, similar to findings of other studies evaluating the addition of new agents to alkylators and steroids in MM (49). Both Phase III and II studies on untreated overt MM patients who were ineligible for HDC/auto-HSCT and eligible, respectively (JCOG0112 and JCOG0005-DI), were terminated early because of poor patient accrual and the results of a planned interim analysis, respectively (50).…”
Section: Multiple Myelomasupporting
confidence: 55%
“…A Phase II study of COP (cyclophosphamide, prednisolone) -MP (melphalan, prednisolone) for untreated overt MM patients (JCOG8906) revealed a similar efficacy to those from the USA and Europe (48). A subsequent randomized Phase III study comparing modified (m)COP-MP with/without ranimustine for untreated overt MM (JCOG9301) revealed that addition of ranimustine to mCOP/ MP has no benefit for survival, despite improving the response rate and PFS, similar to findings of other studies evaluating the addition of new agents to alkylators and steroids in MM (49). Both Phase III and II studies on untreated overt MM patients who were ineligible for HDC/auto-HSCT and eligible, respectively (JCOG0112 and JCOG0005-DI), were terminated early because of poor patient accrual and the results of a planned interim analysis, respectively (50).…”
Section: Multiple Myelomasupporting
confidence: 55%
“…13,14 In previously untreated patients with MM, melphalan + prednisolone (MP), MP-like regimens, and vincristine + doxorubicin + dexamethasone (VAD) have been frequently applied. [15][16][17][18] Several but not all randomized controlled trials have shown that high-dose chemotherapy followed by autologous stem cell transplantation (SCT) is superior to conventional-dose chemotherapy in terms of response rate and progression-free and overall survivals, [19][20][21] and highdose chemotherapy is recommended for MM patients 65 years of age or younger as a part of the initial therapy.…”
mentioning
confidence: 99%